Limb development: how Drosophila genetics can be used to understand pattern formation - Basler, Konrad (Henry Stewart Talks, 2008)
Positional information and cell-cell communication, Drosophila wing development, Gradient versus sequential induction mechanisms, Compartment boundaries and cell affinities, The Dpp morphogen
Reviewed at 2018/05/31